Effectiveness of omalizumab in patients with severe allergic asthma with and without chronic rhinosinusitis with nasal polyps: a PROXIMA study post hoc analysis - Enrico Heffler; Fabiana Saccheri; Marta Bartezaghi; Giorgio Walter Canonica (Clinical and Translational Allergy, 2020)
Abstract Background A significant proportion of patients with severe asthma may also suffer from nasal polyposis, which is commonly defined as chronic rhinosinusitis with nasal polyps (CRSwNP), the presence of which may adversely affect asthma treatment outcomes. The biologic agent omalizumab is effective as add-on therapy in patients with severe allergic asthma. The aim of this post hoc analysis of the PROXIMA study was to compare the efficacy of omalizumab between patients with severe allergic asthma, with and without comorbid CRSwNP. Methods PROXIMA was a prospective observational 2-part study conducted in Italy in adult patients with severe allergic asthma, where, in the second part, patients eligible for add-on omalizumab initiated treatment for 12 months. Patient baseline data such as comorbidities and history of exacerbations were collected. Outcomes were asthma control (Asthma Control Questionnaire [ACQ]), lung function (forced expiratory volume in 1 s [FEV1]) and exacerbation rate. The post hoc analysis compared these outcomes between the cohort with comorbid CRSwNP and the cohort without CRSwNP. Results Of 123 patients included in this analysis, 17 (13.8%) were in the CRSwNP cohort. There was no significant difference between cohorts in baseline clinical characteristics or in change from baseline at 12 months in ACQ values,  % of predicted FEV1 or annual asthma exacerbation rate, although results were numerically in favor of the CRSwNP cohort versus the non-CRSwNP cohort. The proportion of patients who achieved an improvement in all three outcomes was numerically greater in the CRSwNP cohort (35.7% vs 23.0%). Conclusions In an observational real-world setting, add-on omalizumab for severe allergic asthma was effective in improving asthma control, lung function and in reducing exacerbations, including in those patients with CRSwNP.